1991
DOI: 10.1128/iai.59.1.36-44.1991
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immunity induced by the affinity-purified 21-kilodalton zygote-ookinete surface antigen of Plasmodium berghei

Abstract: By using affinity-purified ookinete surface antigen from the rodent malaria parasite Plasmodium berghei, a transmission-blocking immunity was induced in mice. Groups of mice were immunized via different routes, with total quantities of antigen ranging from 0.5 to 40 ,ug (with or without Freund adjuvant). Vaccination by the intramuscular route with 20 ,ug of antigen in the absence of adjuvant and boosted once with the same amount of protein induced a total transmission blockade. Immunoblot analysis confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
(39 reference statements)
2
28
0
Order By: Relevance
“…The immunity induced reduced transmission of the parasite from the gametocyte infected host to the mosquito vector, but less effectively than the native antigen. We recorded an average reduction in intensity of infection of 33% compared to the 63-100% blockade inducible by the native antigen (Tirawanchai et al 1991). This immunity did not modify the bloodstage infection in any of the parameters measured (parasitaemia, gametocytaemia or exflagellation), which is consistent with earlier studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The immunity induced reduced transmission of the parasite from the gametocyte infected host to the mosquito vector, but less effectively than the native antigen. We recorded an average reduction in intensity of infection of 33% compared to the 63-100% blockade inducible by the native antigen (Tirawanchai et al 1991). This immunity did not modify the bloodstage infection in any of the parameters measured (parasitaemia, gametocytaemia or exflagellation), which is consistent with earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…1993). In contrast specific (polyclonal) anti-Pbs2 1 IgG concentration in mice immunized with the native antigen correlated closely with the blockade induced, such that sera containing levels of IgG calculated to be greater than 100 pg/ml were invariably found to block transmission completely (Tirawanchai et al 1991). Here we found that Ig levels higher than 100 pg/ml when induced by the recombinant molecule did not induce a total blockade.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Fertilization ensues within about 1 h. There is no evidence of chemotaxis between the male and female gametes. Factors derived from both the vector and the vertebrate host, the latter including antibodies (Tirawanchai et al ., 1991;Kaslow, 1993;Yoshida et al ., 1999), complement (Grotendorst et al ., 1986;Healer et al ., 1997;Margos et al ., 2001), cytokines (Motard et al ., 1993;Naotunne et al ., 1993), leukocytes (Rutlege et al ., 1969;Sinden and Smalley, 1976) and the biochemical composition of the bloodmeal (Billker et al ., 1997) all contribute to success or failure of these events.…”
Section: The Mature Gametocytementioning
confidence: 99%